Peran Guru Pendidikan Agama Islam dalam Menginternalisasikan Nilai Akhlak dan Moderasi Beragama di Tengah Tantangan Media Sosial Pada Siswa Sekolah Menengah Atas - Siti Patimah; Nur Annisa; Nur Azizah (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
The development of digital technology, particularly social media, has made it easier for students to access religious information, but it has also posed challenges in the form of the dissemination of information that does not always align with moral values and religious moderation. In this context, Islamic Religious Education (IRE) teachers play a crucial role in guiding students to properly understand and internalize these values in the digital age. This study employs a qualitative approach with a descriptive research design. The study was conducted at SMAS Dwimas Sejati, with PAI teachers as the primary informants and students as supporting informants. Data collection techniques included interviews and documentation, while data analysis utilized an interactive model encompassing data reduction, data presentation, and drawing conclusions, with data validity ensured through triangulation. The results of the study indicate that the role of PAI teachers in internalizing moral values is carried out through setting a good example and fostering habits; the role of teachers in instilling religious moderation is achieved by cultivating attitudes of tolerance and respect for differences; the strategies employed include linking course material to the realities of social media and providing continuous guidance; supporting factors stem from the active role of teachers and the school environment, while the main inhibiting factors and challenges are the strong influence of social media on students’ behavior and mindset. This study concludes that Islamic Education teachers play a strategic role in instilling moral values and religious moderation, but their success is greatly influenced by environmental support and students’ ability to use social media wisely.